PERANAN BEA DAN CUKAI DALAM MEMBERANTAS PENYELUNDUPAN NARKOTIKA DI PELABUHAN TUNON TAKA NUNUKAN - Nur Ayuni; Manan Sailan; Heri Tahir (Jurnal Tomalebbi, 2019)
ABSTRACT, This article describes the role of Customs and Excise in Combating Narcotics Smuggling in Tunon Taka Nunukan Port. This study aims to determine: 1) The role of customs and excise in combating narcotics smuggling in the Tunon Taka Nunukan port. 2) Constraints faced by Customs and Excise in combating narcotics smuggling in Tunon Taka Nunukan Port. 3) the solution of the obstacles faced by Customs and Excise in combating narcotics smuggling in Tunon Taka Nunukan Port The research method used in this thesis is a qualitative descriptive technique with data collection techniques namely interviews and documentation. By using primary data sources from 3 informants from Customs and Excise officers in charge of the investigation and prosecution section. Data obtained from the results of the study were processed using descriptive qualitative analysis techniques. Based on the results of the study, namely: 1) Perana Customs and Excise in combating narcotics smuggling is by conducting patrols and also carrying out the duties and functions of the Customs and Excise. 2) Constraints faced by Customs and Excise are the lack of personnel so that Customs and Excise work cannot be carried out to the maximum extent possible and the lack of detection devices in several locations that are often found in cases of drug smuggling. 3) The solution to the obstacles faced by Customs and Excise in combating narcotics smuggling is by cooperating with the National Narcotics Agency (BNN) and the police in order to facilitate Customs and Excise in combating Narcotics smuggling.ABSTRAK, Artikel ini menguraikan masalah Peranan Bea dan Cukai Dalam Memberantas Penyelundupan Narkotika di Pelabuhan Tunon Taka Nunukan. Penelitian ini bertujuan untuk mengetahui : 1)Peranan Bea dan Cukai dalam memberantas penyelundupan narkotika di pelabuhan Tunon Taka Nunukan. 2) Kendala yang di hadapi Bea dan Cukai dalam memberantas penyelundupan narkotika di Pelabuhan Tunon Taka Nunukan. 3) solusi dari kendala yang di hadapi Bea dan Cukai dalam memberantas penyelundupan narkotika di Pelabuhan Tunon Taka Nunukan Metodepenelitian yang digunakan dalam skripsi adalah deskriptif kualitatif dengan teknik pengumpulan data yakni wawancara dan dokumentasi.Dengan menggunakan sumber data primer dari 3 informan dari petugas Bea dan Cukai yang bertugas dibagian penyelidikan dan penindakan. Data yang diperoleh dari hasil penelitian diolah dengan menggunakan teknik analisis secara deskriptif kualitatif. Berdasarkan Hasil penelitian yaitu: 1) Perana Bea dan Cukai dalam memberantas penyelundupan narkotika yaitu dengan mengadakan patroli dan juga menjalankan tugas dan fungsi dari Bea dan Cukai tersebut. 2) Kendala yang dihadapi Bea dan Cukai yaitu kurangnya personil sehingga membuat kerja Bea dan Cukai tidak dapat dijalankan semaksimal mungkin dan kurangnya alat pendeteksi dibeberapa lokasi yang sering didapatkan kasus penyelundupan narkotika. 3) Solusi dari kendala yang dihadapi pihak Bea dan Cukai dalam memberantas penyelundupan narkotika yaitu dengan mengadakan kerja sama dengan Badan Narkotika Nasional (BNN) dan pihak kepolisian agar dapat memudahkan Bea dan Cukai dalam memberantas penyelundupan Narkotika tersebut.